Combined partial denitrification-anammox with urea hydrolysis (U-PD-Anammox) process: A novel economical low-carbon method for nitrate-containing wastewater treatment. (15th January 2023) - Zhang, Chuchu; Guo, Lu; Qin, Jiafu; Chen, Zhenguo; Deng, Zexi; Wang, Xiaojun
Abstract: For the sake of exploring a new economical and low-carbon alternative for real nitrate-containing wastewater treatment, a new combined partial denitrification-anammox with urea hydrolysis (U-PD-Anammox) process was developed. The nitrogen removal performance of this process was investigated through long-term operation in a sequencing batch reactor (SBR) and two submerged anaerobic biological filters (SABF). Results showed that the average NO3 − -N to NO2 – N transformation ratio improved to 82.6% with organic carbon source to NO3 – N ratio of 1.8, and urea hydrolysis provided sufficient NH4 + -N and inorganic carbon to anammox process for nitrogen removal. The influent NH4 + -N/NO2 − -N ratio for subsequent anammox reactor could be adjacent to the optimal ratio of 1.32 during the whole operation. The combined process showed efficient nitrogen removal performance with 85% NO3 − -N removal, 93.8% total nitrogen removal and total nitrogen loading rate as 1.1 ± 0.5 kg N/(m 3 ·d). High-throughput sequencing analysis results revealed that Genera Thauera, Hyphomicrobium and Candidatus Brocadia were the dominant species responsible for partial denitrification, urea hydrolysis and anammox, respectively. The proposed process was more economically and environmental-friendly than the traditional denitriﬁcation process with 51.7% operational cost reduction, 99.7% N2 O and 60% CO2 emission decrement, facilitating the sustainable development of the nitrate-containing wastewater treatment industry in the future. Graphical abstract: Image 1 Highlights: Anammox was applied for real nitrate wastewater treatment by urea hydrolysis and PD. Carbon sources step-feeding facilitated quick start-up of partial denitrification. 82.6% of NO3 – N converted to NO2 – N was achieved with a low COD/NO3 − -N ratio of 1.8. Urea can supply NH4 + -N and inorganic C for anammox in treating nitrate wastewater. The process reduced 51.7% cost, 97% N2 O, 60% CO2 versus complete denitrification.